A New Apparatus for Recording Evoked Responses to Painful and Non-painful Sensory Stimulation in Freely Moving Mice - Zhang, Jiaojiao; Embray, Lee; Yanovsky, Yevgenij; Brankačk, Jurij; Draguhn, Andreas (Frontiers in Neuroscience, 2021)
Experiments on pain perception in animals face several methodological challenges including the reproducible application of painful stimuli. Ideally, behavioral and physiological correlates of pain should be assessed in freely behaving mice, avoiding stress, fear or behavioral restriction as confounding factors. Moreover, the time of pain-evoked brain activity should be precisely related to the time of stimulation, such that pain-specific neuronal activity can be unambiguously identified. This can be achieved with laser-evoked heat stimuli which are also well established for human pain research. However, laser-evoked neuronal potentials are rarely investigated in awake unrestrained rodents, partially due to the practical difficulties in precisely and reliably targeting and triggering stimulation. In order to facilitate such studies we have developed a versatile stimulation and recording system for freely moving mice. The custom-made apparatus can provide both laser- and mechanical stimuli with simultaneous recording of evoked potentials and behavioral responses. Evoked potentials can be recorded from superficial and deep brain areas showing graded pain responses which correlate with pain-specific behavioral reactions. Non-painful mechanical stimuli can be applied as a control, yielding clearly different electrophysiological and behavioral responses. The apparatus is suited for simultaneous acquisition of precisely timed electrophysiological and behavioral evoked responses in freely moving mice. Besides its application in pain research it may be also useful in other fields of sensory physiology.